1987
DOI: 10.1083/jcb.105.2.705
|View full text |Cite
|
Sign up to set email alerts
|

Early hypomethylation of 2'-O-ribose moieties in hepatocyte cytoplasmic ribosomal RNA underlies the protein synthetic defect produced by CCl4.

Abstract: Abstract. Carbon tetrachloride (CCL) treatment of rats produces an early defect in methylation of hepatocyte ribosomal RNA, which occurs concurrently with a defect in the protein synthetic capacity of isolated ribosomes. The CCh-induced methylation defect is specific for the 2'-O-ribose position, and a corresponding proportional increase in mTG base methylation occurs in vivo. Undermethylated ribosomal subunits (rRNA) from CCl4-treated preparations can be methylated in vitro to a much greater extent than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, supplementation with GE induced serum albumin levels in the CCl 4  + MGE and CCl 4  + HGE groups that were close to those of the CCl 4  + silymarin group (26.6 ± 2.4 g/L and 26.7 ± 3.1 g/L vs. 27.1 ± 2.2 g/L, respectively) and significantly higher than those of the CCl 4 group ( p  < 0.05). Previous studies have found that CCl 4 decreased serum total protein and albumin in carps [35], inhibited protein synthesis, and reduced ribosomal RNA methylation [36]. Administration of CCl 4 could inhibit the synthesis of albumin and other proteins in the liver, and result in significantly lower serum albumin level [37].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, supplementation with GE induced serum albumin levels in the CCl 4  + MGE and CCl 4  + HGE groups that were close to those of the CCl 4  + silymarin group (26.6 ± 2.4 g/L and 26.7 ± 3.1 g/L vs. 27.1 ± 2.2 g/L, respectively) and significantly higher than those of the CCl 4 group ( p  < 0.05). Previous studies have found that CCl 4 decreased serum total protein and albumin in carps [35], inhibited protein synthesis, and reduced ribosomal RNA methylation [36]. Administration of CCl 4 could inhibit the synthesis of albumin and other proteins in the liver, and result in significantly lower serum albumin level [37].…”
Section: Resultsmentioning
confidence: 99%
“…uitro translations were performed using a nucleasetreated rabbit reticulocyte lysate system (Bethesda Research Laboratories, Gaithersburg, MD), with 35s-methionine (New England Nuclear) and 1.2 pg poly(A)+ RNA. Previous experimentation (26) showed that mRNA was rate limiting under these conditions. Total incorporation was measured as described (26).…”
Section: Methodsmentioning
confidence: 95%
“…Previous experimentation (26) showed that mRNA was rate limiting under these conditions. Total incorporation was measured as described (26). Immunoprecipitations with solubilized translation products used a monoclonal antibody (G18) that recognized lamins A/C on immunoblots and anti-mouse-IgM- which is the reverse complement of nucleotide region 1210-1233 from human lamin A and C (16,29).…”
Section: Methodsmentioning
confidence: 95%
“…), absorbance detector, fraction collector, radial compressed C,, u-bondapak reverse-phase column, a flow rate of 1 mlimin and a linear gradient of 0% to 30% acetonitrile from 0 to 40 min. Some analytical separations were as previously reported (4). These conditions were chosen to yield good separations of the major (and minor) methylated nucleosides; 0.3 ml fractions were collected and counted.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps the earliest metabolic defect in CC14-induced injury is a profound depression of PS (1)(2)(3). Recently, we found that CC1, injury is associated with an early hypomethylation of ribosomal RNA (rRNA) (4). For a variety of reasons, this methylation defect seems to be cyto-plasmic in nature and is specific for 2'-O-ribose moieties on purine nucleotides.…”
Section: -434)mentioning
confidence: 98%